2009
DOI: 10.1021/ja902889s
|View full text |Cite
|
Sign up to set email alerts
|

Efficient C−B Bond Formation Promoted by N-Heterocyclic Carbenes: Synthesis of Tertiary and Quaternary B-Substituted Carbons through Metal-Free Catalytic Boron Conjugate Additions to Cyclic and Acyclic α,β-Unsaturated Carbonyls

Abstract: Metal-free, nucleophilic activation of a B-B bond has been exploited in the development of a highly efficient method for conjugate additions of commercially available bis(pinacolato)diboron to cyclic or acyclic α,β-unsaturated carbonyls. Reactions are readily catalyzed by 2.5-10 mol % of a simple N-heterocyclic carbene (NHC). A variety of cyclic and acyclic unsaturated ketones and esters can serve as substrates. Transformations deliver β-boryl carbonyls bearing tertiary as well as quaternary B-substituted carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
101
1
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(113 citation statements)
references
References 30 publications
3
101
1
8
Order By: Relevance
“…This field has recently been elegantly reviewed by Oestreich and co-workers, [6] and the authors conclude that asymmetric metal-free approaches to conjugate borylation might be the next pioneering step forwards. Hoveyda and coworkers recently reported an efficient metal-free b-boration of cyclic and acyclic a,b-unsaturated carbonyl groups promoted by N-heterocyclic carbenes (NHCs).[7] Mechanistic studies revealed that 10 mol % of carbene alone can activate the diboron reagent, bis(pinacolato)diboron (B 2 pin 2 ), by nucleophilic attack at one of the boron atoms (Scheme 1).After 1,4-addition of the reagent to the substrate the carbene is regenerated, this making the reaction catalytic.Attempts by Hoveyda and co-workers [7] to promote the bboration of 2-cyclohexen-1-one with PPh 3 and PCy 3 as nucleophilic reagents in the absence of a metal were unsuccessful. However, an early example by Hosomi and co-workers [8] showed that PBu 3 could induce slight conversion of benzylideneacetophenone into the b-borated ketone in the absence of the catalyst precursor CuOTf (Scheme 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This field has recently been elegantly reviewed by Oestreich and co-workers, [6] and the authors conclude that asymmetric metal-free approaches to conjugate borylation might be the next pioneering step forwards. Hoveyda and coworkers recently reported an efficient metal-free b-boration of cyclic and acyclic a,b-unsaturated carbonyl groups promoted by N-heterocyclic carbenes (NHCs).[7] Mechanistic studies revealed that 10 mol % of carbene alone can activate the diboron reagent, bis(pinacolato)diboron (B 2 pin 2 ), by nucleophilic attack at one of the boron atoms (Scheme 1).After 1,4-addition of the reagent to the substrate the carbene is regenerated, this making the reaction catalytic.Attempts by Hoveyda and co-workers [7] to promote the bboration of 2-cyclohexen-1-one with PPh 3 and PCy 3 as nucleophilic reagents in the absence of a metal were unsuccessful. However, an early example by Hosomi and co-workers [8] showed that PBu 3 could induce slight conversion of benzylideneacetophenone into the b-borated ketone in the absence of the catalyst precursor CuOTf (Scheme 2).…”
mentioning
confidence: 99%
“…Hoveyda and coworkers recently reported an efficient metal-free b-boration of cyclic and acyclic a,b-unsaturated carbonyl groups promoted by N-heterocyclic carbenes (NHCs). [7] Mechanistic studies revealed that 10 mol % of carbene alone can activate the diboron reagent, bis(pinacolato)diboron (B 2 pin 2 ), by nucleophilic attack at one of the boron atoms (Scheme 1).…”
mentioning
confidence: 99%
“…[82] Mit Blick auf organokatalytische Reaktionen beobachteten Hoveyda und Mitarbeiter, dass das 1,4-Addukt 109 als einziges Diastereomer gebildet wurde, wenn das Enon 107 mit Bis(pinacolato)dibor (108) und einem in situ erzeugten NHC reagierte (Schema 23). [83] Der NHC-Diboran-Komplex 110 wurde hierbei als Intermediat im Katalysezyklus vorgeschlagen.…”
Section: Katalyse Mit Nhc-boranenunclassified
“…Multicomponent reactions have now been extended to reactions involving five, six or even eight components by the introduction of orthogonal functional groups 39 . Some random highlights deserving a mention include: a site-selective glycosylation of hydroxyketones at the ketone or the alcohol via hydrosilylation 40 ; a transition metal-free reductive C−C coupling of tosylhydrazones and aromatic or aliphatic boronic acids 41 ; N-heterocyclic carbene-catalyzed 1,4-addition-α-hydroxyalkylation of α,β-ethylenecarbonyl compounds with bis(pinacolato)diborane 42 ; a catalytic Wittig synthesis starting from bromides and aldehydes with regeneration of the [cyclic] phosphine using diphenylsilane 43 ; a biocatalytic equivalent of Friedel-Crafts allyl-, benzyl-or propargyl-ation using S-adenosyl-L-methionine and methyltransferases 44 ; and a synthesis of 2-functionalized pyrimidines/quinazolines from cyanic acid derivatives and enacylamines/anilides, providing a route to C2-and C4-substituted compounds 45 . To conclude, it is notable that it is now possible to predict new molecular targets for known drugs computationally 46 ; this involves systematically defining each target by its ligands then looking for chemical similarities with the drugs.…”
Section: Further Trends and Developments In Synthetic Organic Chemistmentioning
confidence: 99%